2013
DOI: 10.1002/mnfr.201300322
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic metabolites of anthocyanins following a dietary intervention study in post‐menopausal women

Abstract: Scope: Numerous studies feeding anthocyanin-rich foods report limited bioavailability of the parent anthocyanins. The present study explores the identity and concentration of the phenolic metabolites of anthocyanins in humans. Methods and results: Anthocyanin metabolites were quantified in samples collected from a previously conducted 12-wk elderberry intervention study in healthy post-menopausal women. Individual 1-, 2-and 3-h post-bolus urine samples and pooled plasma samples following acute (single bolus) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
123
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(137 citation statements)
references
References 47 publications
10
123
0
Order By: Relevance
“…However, Curtis et al [119] indicate the consumption of 500 mg/day of elderberry extract for 12 weeks is ineffective in reducing the risk of CVD in healthy postmenopausal women. There is also no change in metabolic processing following 12 weeks of elderberry intake compared with acute intake [120]. …”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 99%
“…However, Curtis et al [119] indicate the consumption of 500 mg/day of elderberry extract for 12 weeks is ineffective in reducing the risk of CVD in healthy postmenopausal women. There is also no change in metabolic processing following 12 weeks of elderberry intake compared with acute intake [120]. …”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 99%
“…Microbiota can degrade anthocyanins to phenolic acids and aldehydes by splitting the C-ring and modifying the remaining A and B-rings (62) . Some of the main metabolites of microbiota degradation are gallic acid, vanillic acid, homovanilic acid, protocatechuic acid (PCA), syringic acid and 4-hydroxybenzoic acid (55,(65)(66)(67)(68) . Despite knowledge of the high rate of anthocyanin degradation by gut microbiota there is still no consensus about the proportion absorbed into the systemic circulation (45,53,55) .…”
Section: Bioavailability Of Anthocyaninsmentioning
confidence: 99%
“…For example, a study published in 2007 reported only the recovery of cyanidin-3-glucoside and PCA in the plasma following ingestion of 1 litre blood orange juice (65) . However, de Ferrars et al (55) in 2013 reported twenty-eight total metabolites, seventeen phenolics and eleven anthocyanin conjugates in urine following consumption of an elderberry extract (500 mg mixed anthocyanins) consisting mostly of cyanidin glycosides, while plasma analysis discovered seventeen phenolics and four anthocyanin conjugates. Urine samples demonstrated high amounts of vanillic acid and conjugates and were more abundant in anthocyanin conjugates, while the plasma was highest in 4-hydroxybenzaldehyde and PCA-sulphate (55) .…”
Section: Bioavailability Of Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work suggests that the bioavailability of berry (poly)phenols is higher and more complex than previously thought [9,[19][20][21]. Highly unstable anthocyanins are degraded into smaller compounds as early as 1 hour postconsumption, before or after being absorbed in the small intestine, leading to a vast array of phenolic metabolites that can be glucuronidated, sulfated and/or methylated and circulate in much higher concentrations than the structurally related anthocyanin metabolites [19,22,23].…”
Section: Introductionmentioning
confidence: 99%